Pengembangan Lembar Kerja Siswa Berbasis Pendekatan Contextual Teaching and Learning Berbantuan Geogebra Materi Segi Empat Kelas VII SMP - Vassa, Wahyuni Andicha (Unika Santo Thomas Medan, 2019)
This study aims to 1) find out the validity of the use of Student Worksheets (LKS) based on the CTL approach, 2) determine the effectiveness of using Student Worksheets (LKS) based on the CTL approach so that it can be used in the Quadrilateral Build Flat material class VII Padang Bulan GKPI Private Middle School Field. This research is a research development (R & D) using the ADDIE learning development model with stages (1) Analysis (Analisis),Â (2) Design (Design), (3) Develop (Development), (4) Implement (Implementation), (5) Evaluation (Evaluation). Based on the results of data analysis and discussion, it was obtained data from expert validation results with an average total rating of 4.25 in the very good category so that the LKS was said to be valid and feasible to use. The effectiveness of the LKS based on the CTL approach with the help of GeoGebra was seen from a number of assessments obtained through learning outcomes tests which included: 1) Classical learning completeness of students at 85.18% in the complete category; (2) Achievement of competency indicators with a percentage of 80.08% in the complete category; (3) The results of the observation of the teacher's ability to manage learning with an average value of 3.72 are in the very good category; (4) Effective learning time for four times; (5) Questionnaire of student responses to student worksheets with an average rating of 5.50 is in a very good category and every aspect is responded positively. Based on the results of the above data analysis, it can be concluded that the development of Student Worksheets (LKS) is based on the Contextual Teaching and Learning (CTL) approach with the help of GeoGebra in the quadrangular Build Flat class VII GKPI Private Middle School Padang Bulan Medan is valid and effective used in supporting the process of learning mathematics.